ADAP plays a pivotal role in CD4+ T cell activation but is only marginally involved in CD8+ T cell activation, differentiation, and immunity to pathogens. Issue 2 (7th September 2016) - Parzmair, Gerald P; Gereke, Marcus; Haberkorn, Oxana; Annemann, Michaela; Podlasly, Lisa; Kliche, Stefanie; Reinhold, Annegret; Schraven, Burkhart; Bruder, Dunja
Abstract: The adhesion and degranulation promoting adaptor protein (ADAP) is a multifunctional scaffold involved in many different signaling pathways that are important for the function of T cells, including the inside-out and outside-in signaling of integrins, the activation of NF-κB, and the subsequent production of proinflammatory cytokines (e.g., IFN-γ and IL-2). Strikingly, despite its well-established role in T cells, previous studies did not distinguish between CD4 + and CD8 + T cells, and thus, it is unknown whether ADAP fulfills equally important functions in both T cell subsets. We show here that despite comparable ADAP expression levels in CD4 + and CD8 + T cells, their function is differentially dependent on ADAP. Whereas in vitro TCR-stimulation experiments revealed that activation, proliferation, and adhesion are severely compromised in CD4 + T cells lacking ADAP, their CD8 + counterparts are hardly affected by ADAP deficiency. Accordingly, antigen-specific in vivo stimulation of adoptively transferred CD8 + T cells during Listeria monocytogenes ( Lm ) and influenza A virus (IAV) infection revealed only moderate effects of ADAP deficiency in terms of CD8 + T cell activation, proliferation, and differentiation, which, however, did not impair pathogen-specific immunity. Thus, we show for the first time that ADAP fulfills different functions in CD4 + and CD8 + T cells, with CD8 + T cells being less dependent on ADAP. Our data identify ADAP as a potential molecular target for T cell subset-specific therapeutic interventions.